Aktivitas Antischistosomiasis Sediaan Nanopartikel Ekstrak Biji Pinang pada Tikus Putih Jantan Terinfeksi Schistosoma japonicum: The Antischistosomiasis Activity Test on Nanoparticles Ethanolic Extract of Betel Nut to Male Rats Infected with Schistosoma japonicum - Marzela Dewi; David Pakaya; Joni Tandi (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Schistosomiasis is a disease caused by Schistosoma japonicum worms and Oncomelania hupensis lindoensis as the intermediate snails. Praziquantel is a drug used to reduce the prevalence of schistosomiasis. However, its use has several side effects such as headaches, dizziness, nausea, vomiting as well as abdominal, joint, and muscle pain. The development of alternative drugs is a solution to reduce side effects. Betel (A. catechu) seeds are known to the public to have an anthelmintic effect because they contain alkaloids, tannins, flavan, phenolic compounds, as well as arecoline. To increase the bioavailability and efficacy of the extract, the seeds were prepared in the formulation of nanoparticles. This study aims to determine the antischistosomiasis activity of the ethanol extract nanoparticles of betel nut as an antischistosomiasis. The rats were divided into 9 treatment groups consisting of normal, negative and positive control groups, extract treatment and treatment of nanoparticle preparations with dose variations of 30, 60, and 120 mg/kgBW. The parameter observed was the number of S. japonicum eggs in rat feces before and after treatment. Data obtained from the mean number of S. japonicum eggs was tested for normality with Saphiro-Wilk test, and showed that the data were not normally distributed. Furthermore, nonparametric statistical analysis was carried out with Kruskal-Wallis which showed there was no significant difference in the mean number of S. japonicum eggs in all treatment groups. The results showed that the ethanol extract nanoparticles of A. catechu had antischistosomiasis activity.